2015
DOI: 10.1037/ser0000057
|View full text |Cite
|
Sign up to set email alerts
|

Predicting utilization of healthcare services in the veterans health administration by returning women veterans: The role of trauma exposure and symptoms of posttraumatic stress.

Abstract: Combat exposure and military sexual trauma (MST) are prevalent among returning women Veterans and associated with increased alcohol use and psychological distress. However, it remains unclear the extent to which combat exposure and MST are associated with utilization of healthcare in the Veterans Health Administration (VHA). The current study explored the relationships among alcohol use and distress in women who deployed in support of Operations Enduring Freedom, Iraqi Freedom, and New Dawn (OEF/OIF/OND). It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Twenty-one studies assessed the relation between MST and alcohol. Findings were mixed, with some studies documenting significant positive relations between MST and alcohol use (Hahn et al, 2015) and misuse (Creech & Borsari, 2014; Fillo et al, 2018; Frayne et al, 2003; Gradus et al, 2008; Hahn et al, 2015; Hankin et al, 1999; Hoggatt et al, 2015; Ryan et al, 2015), and others finding no relation between MST and alcohol use (Beckman et al, 2018; Godfrey et al, 2015; Jenkins et al, 2015; Rowe et al, 2009; Schuyler et al, 2017), and misuse (Gobin et al, 2015; Katz et al, 2012; Klingensmith et al, 2014; Maguen et al, 2012; Schry et al, 2015; Stahlman et al, 2014; Tiet et al, 2015; Yalch et al, 2018). Seven studies assessed the relation between MST and drugs.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one studies assessed the relation between MST and alcohol. Findings were mixed, with some studies documenting significant positive relations between MST and alcohol use (Hahn et al, 2015) and misuse (Creech & Borsari, 2014; Fillo et al, 2018; Frayne et al, 2003; Gradus et al, 2008; Hahn et al, 2015; Hankin et al, 1999; Hoggatt et al, 2015; Ryan et al, 2015), and others finding no relation between MST and alcohol use (Beckman et al, 2018; Godfrey et al, 2015; Jenkins et al, 2015; Rowe et al, 2009; Schuyler et al, 2017), and misuse (Gobin et al, 2015; Katz et al, 2012; Klingensmith et al, 2014; Maguen et al, 2012; Schry et al, 2015; Stahlman et al, 2014; Tiet et al, 2015; Yalch et al, 2018). Seven studies assessed the relation between MST and drugs.…”
Section: Resultsmentioning
confidence: 99%
“…52 One article investigated military trauma related to sexual minority status. 120 Estimates of trauma prevalence were primarily unadjusted and mostly consistent across articles, with five articles finding higher prevalence among engaged Veterans, 52,59,88,115,120 and one showing mostly no difference. 107 No articles examined the role of trauma in health behaviors, health services utilization, or health outcomes for engaged and non-engaged Veterans.…”
Section: Traumamentioning
confidence: 92%
“…Articles on engaged and non-engaged Veterans also employed different measures and studied various trauma exposures (online Appendix Table 6). One article examined adverse childhood experiences and adult experience of sexual trauma or IPV, 88 three articles addressed combatrelated trauma and sexual or non-combat-related physical trauma during military service, 88,107,115 one article examined history of military sexual assault, 59 and one article examined Vietnam war-zone service. 52 One article investigated military trauma related to sexual minority status.…”
Section: Traumamentioning
confidence: 99%
“…For instance, Koblinsky et al, (2017), found that homelessness and suicide among women veterans, is at a far greater rate than civilians and Hoffmire, Kemp, and Bossarte (2015) suggest a 40% increase in suicide over ten-years. All contributing to the growing understanding that exposure to war, trauma and MST increases the risk of PTSD (Magruder et al, 2015;Ryan, McGrath, Creech, and Borsari, 2015) and is likely attributable to the physical and mental health needs of women veterans now and in the future.…”
Section: Experiences After the Militarymentioning
confidence: 99%